2013
DOI: 10.2494/photopolymer.26.817
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Chemoepitaxy of Block Copolymer Thin Films using Self-Consistent Field Theory

Abstract: Directed self-assembly (DSA) of block copolymers (BCPs) is a promising technology for advanced patterning at future technology nodes. We use Self-Consistent Field Theory (SCFT) to model directed self-assembly (DSA) of PS-PMMA block copolymers on chemically patterned surfaces (chemoepitaxy). We consider the scenario in which the surface is covered by a neutral brush, in which PS-preferential guiding lines are written. The lines have width W and the period of the line pattern is denoted as P. After the DSA proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…[28][29][30][31][32] Russell and co-workers investigated the unconventional morphologies of symmetric, diblock copolymers as a function of film thickness, 28 and interfacial interactions as early as 1990s. 50,[57][58][59][60][61][62][63][64][65][66] Ross and co-workers successfully explored the graphoepitaxy of spherical morphological block copolymers templated by an array of posts, predicting that the formation of aperiodic templated structures gave an excellent agreement with experimental results. 32 In the following, a series of experimental studies have demonstrated the above results.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…[28][29][30][31][32] Russell and co-workers investigated the unconventional morphologies of symmetric, diblock copolymers as a function of film thickness, 28 and interfacial interactions as early as 1990s. 50,[57][58][59][60][61][62][63][64][65][66] Ross and co-workers successfully explored the graphoepitaxy of spherical morphological block copolymers templated by an array of posts, predicting that the formation of aperiodic templated structures gave an excellent agreement with experimental results. 32 In the following, a series of experimental studies have demonstrated the above results.…”
Section: Introductionmentioning
confidence: 84%
“…56 Especially in recent years, self-consistent field theory (SCFT) has been largely promoted to predict new-fashioned or sophisticated structures versus some phase transitions based on the self-assembly of diblock and triblock copolymers. 50,[57][58][59][60][61][62][63][64][65][66] Ross and co-workers successfully explored the graphoepitaxy of spherical morphological block copolymers templated by an array of posts, predicting that the formation of aperiodic templated structures gave an excellent agreement with experimental results. 50 Meng and Wang carried out a systematic calculation to explore the phase behaviors of symmetric diblock copolymers confined in thin films, observing complex structures of T k (k = 1, 2, 3) combined k layers of regular lamellae with a single layer of perforated lamella for asymmetric surface interactions.…”
Section: Introductionmentioning
confidence: 84%
“…Fluctuations and defects could be thermally generated or induced by interactions with the underlying template. Such phenomena may ultimately limit the viability of directed self assembly for semiconductor manufacturing, because perfection over large areas is a necessary condition for implementation of a new patterning technology. We note that fluctuations and defects could be detected from a properly designed X‐ray scattering experiment, provided that data are analyzed with detailed models that predict both the primary and diffuse scattering.…”
Section: Discussionmentioning
confidence: 99%
“…The computational aspects of DSA of lamellae-forming BCPs using chemoepitaxy strategies have been well studied. 10,[12][13][14]31,39,[42][43][44][45][46][47][48][49][50] However, a common feature of all these studies has been that the background region has been modeled as a uniform surface with a specified surface energy instead of the more realistic picture of grafted brushes of random copolymers. 10,[12][13][14]31,39,[42][43][44][45][46][47][48][49][50] Unlike a hard surface with a specified surface energy, grafted copolymers can modulate their interfacial energies by conformational rearrangements and redistribution of segments.…”
Section: Introductionmentioning
confidence: 99%
“…10,[12][13][14]31,39,[42][43][44][45][46][47][48][49][50] However, a common feature of all these studies has been that the background region has been modeled as a uniform surface with a specified surface energy instead of the more realistic picture of grafted brushes of random copolymers. 10,[12][13][14]31,39,[42][43][44][45][46][47][48][49][50] Unlike a hard surface with a specified surface energy, grafted copolymers can modulate their interfacial energies by conformational rearrangements and redistribution of segments. For instance, a previous study using self consistent field theory demonstrated the importance of modeling the random copolymer brush explicitly and the features which arise as a result of this more realistic model.…”
Section: Introductionmentioning
confidence: 99%